Improvement of a rivet geometry for the self-piercing riveting of high-strength steel and multi-material joints - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
As a result of lightweight design, increased use is being made of high-strength steel and aluminium in car bodies. Self-piercing riveting is an established technique for joining these materials. The dissimilar properties of the two materials have led to a number of different rivet geometries in the past. Each rivet geometry fulfils the requirements of the materials within a limited range. In the present investigation, an improved rivet geometry is developed, which permits the reliable joining of two material combinations that could only be joined by two different rivet geometries up until now. Material combination 1 consists of high-strength steel on both sides, while material combination 2 comprises aluminium on the punch side and high-strength steel on the die side. The material flow and the stress and strain conditions prevailing during the joining process are analysed by means of numerical simulation. The rivet geometry is then improved step-by-step on the basis of this analysis. Finally, the improved rivet geometry is manufactured and the findings of the investigation are verified in experimental joining tests.
Keywords: Self-piercing riveting; Joining technology; Rivet geometry; Multi-material design; High-strength steel; Aluminium